ANALISIS PERAN SUKUK SEBAGAI INSTRUMEN NEGARA DALAM MENGENTASKAN KEMISKINAN DI INDONESIA - Adinugroho, Mukhtar (Ekonomi Islam, 2021)
Today the capital market is one of the instruments that play an important role in the economies of both developed and developing countries. For developing countries like Indonesia, the capital market is an economic potential capable of offering solutions to capital problems that are often faced in the context of national development. Especially when efforts to obtain additional capital through loans are felt to be increasingly unprofitable. Likewise with the Islamic capital market, although it is still new when compared to other Islamic financial instruments, the development of the Islamic capital market in Indonesia is considered quite good. One of the Islamic financial instruments that are important financing for the state budget is Sukuk. Domestically, Sukuk has grown quite rapidly, although the proportion is still relatively small compared to conventional markets. This will be able to support the development of the Islamic capital market in Indonesia, especially if it is able to seize the opportunities that exist. One of these opportunities is that waqf assets are widely available in various regions in Indonesia and many of which have not been exploited productively. The dual integration between Sukuk and waqf in Sukuk Al Intifa'a is expected to be able to create a financial instrument that can boost economic development and as an alternative in efforts to alleviate poverty in Indonesia. Keywords: Sukuk, Waqaf, Poverty, Sharia Capital Market